Integrated Reporting Quality Mediates Governance Mechanisms and Firm Value - Anggun Trisnani; Rindu Rika Gamayuni; Pigo Nauli (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Corporate reporting has shifted toward integrated disclosure to address rising demands for transparency, accountability, and long-term value creation. Specific Background Within state-owned enterprises, complex ownership structures and restructuring programs intensify information asymmetry, making credible reporting mechanisms increasingly relevant. Knowledge Gap Prior empirical evidence on the links between corporate governance, capital structure, reporting practices, and firm value remains inconsistent, while studies rarely apply a quality-based measure of Integrated Reporting or examine its mediating role in emerging market SOEs. Aims This study examines whether Integrated Reporting quality mediates the relationships between corporate governance mechanisms, leverage, and firm value in Indonesian state-owned enterprises. Results Using panel data from 21 firms during 2021–2024 and multiple regression with Sobel testing, the findings show that board of directors, board of commissioners, audit committee, and leverage are positively associated with Integrated Reporting quality. Integrated Reporting quality is positively related to firm value and partially mediates the relationships between governance mechanisms, leverage, and firm value, while institutional ownership shows a weaker direct role. Novelty The study introduces a quality-based Integrated Reporting measurement emphasizing coherence, connectivity, and decision usefulness, extending signaling theory within the SOE context. Implications The results underscore Integrated Reporting quality as a strategic transmission mechanism linking governance and financial structure to market valuation, highlighting its relevance for transparency and long-term value creation in state-owned enterprises. Highlights: Internal oversight structures are closely associated with higher coherence and connectivity of corporate disclosures. Reporting quality functions as a transmission mechanism linking oversight arrangements and leverage to market valuation. Capital structure pressures encourage more comprehensive integration of financial and non-financial information. Keywords: Corporate Governance, Integrated Reporting Quality, Firm Value, SOEs